2006
DOI: 10.1007/s10517-006-0115-2
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation potential of mesenchymal stem cells of different origin

Abstract: We compared differentiation potential of mesenchymal stem cells originating from human bone marrow, fatty tissue, thymus, placenta, and skin. The cells were characterized by differentiation into adipocytes and osteoblasts. Mesenchymal stem cells from different sources exhibited different differentiation potential, manifesting by the rate of differentiation and percentage of differentiated cells. Presumably, differentiation of mesenchymal stem cells derived from different tissues can differ due to the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 12 publications
1
63
0
2
Order By: Relevance
“…12,13 Besides, many authors describe MSCs as cells endowed of neoangiogenic, immunomodulatory, antiinflammatory, [14][15][16][17][18] and putative antineoplastic [19][20][21][22] properties, and possibly employable in a plethora of degenerative pathologies. Adipose tissue is composed of two main cell populations, mature adipocytes and stromal vascular fraction (SVF): the latest is an heterogeneous fraction including preadipocytes, endothelial cells, smooth muscle cells, pericytes, macrophages, fibroblasts, [23][24][25] and adipose-derived stem cells (ADSCs), 9,10,24,[26][27][28][29][30][31][32][33] which share several characteristics with bone marrow stem cells. 34 Because of their stemness properties as self-renewal capacity, long-term viability, and multilineage potential, the employ of ADSCs is proposed in tissue engineering and regenerative medicine 6 ; moreover, the use of SVF or ADSCs has been proposed in several chronic pathologies as Crohn disease, 35 graft-versus-host disease, 36 autoimmune pathologies (e.g., multiple sclerosis), 15 and allergic pathologies 37 : the therapeutic approach toward these pathologies can be explained by the immunoregulatory and antiinflammatory activities of ADSCs or nonexpanded SVF cells.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Besides, many authors describe MSCs as cells endowed of neoangiogenic, immunomodulatory, antiinflammatory, [14][15][16][17][18] and putative antineoplastic [19][20][21][22] properties, and possibly employable in a plethora of degenerative pathologies. Adipose tissue is composed of two main cell populations, mature adipocytes and stromal vascular fraction (SVF): the latest is an heterogeneous fraction including preadipocytes, endothelial cells, smooth muscle cells, pericytes, macrophages, fibroblasts, [23][24][25] and adipose-derived stem cells (ADSCs), 9,10,24,[26][27][28][29][30][31][32][33] which share several characteristics with bone marrow stem cells. 34 Because of their stemness properties as self-renewal capacity, long-term viability, and multilineage potential, the employ of ADSCs is proposed in tissue engineering and regenerative medicine 6 ; moreover, the use of SVF or ADSCs has been proposed in several chronic pathologies as Crohn disease, 35 graft-versus-host disease, 36 autoimmune pathologies (e.g., multiple sclerosis), 15 and allergic pathologies 37 : the therapeutic approach toward these pathologies can be explained by the immunoregulatory and antiinflammatory activities of ADSCs or nonexpanded SVF cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, comparative analysis of MSCs derived from various tissues suggest that although they fulfill the general accepted criteria for MSCs, they markedly differ in terms of growth rates, differentiation abilities, colony frequencies, expansion rates, success rates of isolation and gene expression profiles beyond donor and experimental conditions. [17][18][19][20][21][22][23] Perhaps the most attractive aspect of these MSCs is that they can be maintained and propagated in culture for long periods of time without losing their differentiation capacity generating large cell quantities appropriate for clinical applications. Although bone marrow has been the most common source for MSCs, the significant drawback is that the number of bone marrow MSCs and their differentiation potential significantly decrease with age.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, research on the role of adipose tissue in physiology and pathology has been relatively neglected until the discovery of leptin (Zhang et al 1994) and adiponectin (Scherer et al 1995); more recently, adipose tissue has been also identified as a source of mesenchymal stem cells (MSCs) able to differentiate into adipocytes, chondrocytes, osteoblasts, myocytes, cardiomyocytes, hepatocytes, and neuronal, epithelial and endothelial cells (Helder et al 2007;Romanov et al 2005;Dicker et al 2005). Adipose tissue is composed of two main populations, mature adipocytes and stromal vascular fraction (SVF): the latest is a heterogeneous population of cell including preadipocytes, endothelial cells, smooth muscle cells, pericytes, macrophage, fibroblasts (Mizuno and Hyakusoku 2003;Fraser et al 2006;Gomillion and Burg 2006) and adipose MSCs (Romanov et al 2005;Dicker et al 2005;Fraser et al 2006;Rydèn et al 2003;Rodriguez et al 2004Rodriguez et al , 2005Nakagami et al 2006;Strem et al 2005;Musina et al 2006;Guilak et al 2006;Mitchell et al 2006) that share many characteristics of bone marrow MSCs.…”
Section: Introductionmentioning
confidence: 99%